Study on the microstructures of SLM IN718 based on solidification model - XU Wei; WAN Jie; CHEN Yuzeng (Xibei Gongye Daxue Xuebao)
During the selective laser melting(SLM) process of IN718, different process parameters have a significant impact on its microstructure. To analyze the interrelationship between process parameters and microstructure, in this study, the relationship between primary dendrite arm spacing(PDAS) and process parameters was established through a solidification model, and the accuracy of the model was verified through experiments. Both the calculation results and the experimental results show that when the laser power increases, PDAS increases accordingly; while as the scanning speed and hatch distance increase, PDAS decreases accordingly; and from the bottom to the top of the molten pool, PDAS gradually increases. At the same time, the top of the molten pool is more sensitive to the change of process parameters, while the middle and bottom are relatively insensitive. These research results are of certain guiding significance for the microstructure regulation of IN718.